2015
DOI: 10.2527/jas.2015-9520
|View full text |Cite
|
Sign up to set email alerts
|

Shade use by small groups of domestic horses in a hot, sunny environment1

Abstract: Horses in the United States are commonly managed in outside pens or pastures in small groups. Limited research on shade use by domestic horses housed singly in individual pens has shown benefits and a preference for using available shade. The objective of this study was to examine the amount of shade use and the behavioral and physiological responses of small groups of horses when housed with access to shade (SH) and without access to shade (SUN). Thirty-six horses were randomized into 3 consecutive trials usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Horses were proven to prefer shade in hot and sunny environments, and perform more walking and foraging behavior in shaded areas [14,16]. It was also found that horses kept in the sun showed reduced feed intake and movement, while increased amounts of water drunk and time spent close to a drinking point [17]. Thus, shade permitted greater expression of natural behaviors in horses.…”
Section: Introductionmentioning
confidence: 97%
“…Horses were proven to prefer shade in hot and sunny environments, and perform more walking and foraging behavior in shaded areas [14,16]. It was also found that horses kept in the sun showed reduced feed intake and movement, while increased amounts of water drunk and time spent close to a drinking point [17]. Thus, shade permitted greater expression of natural behaviors in horses.…”
Section: Introductionmentioning
confidence: 97%
“…It is also necessary to evaluate their opportunities to engage in behaviours they nd rewarding, including thermal comfort, positive social interactions, resting and feeding behaviours (Mellor, 2016). Behavioural changes related to the presence of shaded areas have been shown both in intensive and extensive systems in several species, such as cattle, sheep, buffaloes, and horses, although previous studies mostly focused on the effect on productive traits (Schütz et al, 2010;Holcomb et al, 2015;Giro et al, 2019;De et al, 2020;Mishra, 2021). Our nding suggested that a shaded area of at least 7 m 2 per animal (our ample category) had bene cial effects on several aspects of the camel's welfare but further studies should de ne speci c recommendations according to the environmental heat load.…”
Section: Discussionmentioning
confidence: 99%
“…According to Chaiybutr et al [ 5 ], heat stress reduces milk production in cattle. Heat stress due to either climate or exercise, or both, has been shown to increase the risk of heat stroke in horses [ 6 ]. Horses have a high metabolic rate but a small surface area for heat dissipation, as described by Janczarek et al [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, horses must be actively cooled, even more so in hot environments. Studies of heat in horses often focus on the effects of exercise and in the paddock [ 6 , 7 , 8 , 9 ]. However, there are few reports on the stall where horses spend the majority of their lives.…”
Section: Introductionmentioning
confidence: 99%